The National Politics of Meat and Carno-Phallogocentrism in Sara Suleri’s Meatless Days - Dr. Munazzah Rabbani, (Al-Qanṭara, 2023)
The invisibility of women in national discourses and the absence of animals as living breathing referents have repeatedly been highlighted by feminists in recent times (Adams & Donovan 2007, Nilsson & Tetreault 2000). In this context, this study focuses on Suleri’s “Meatless Days” (1989) as an allegory of the national politics of meat in Pakistan and probes the role of women and animals in national discourses/narratives as absent referents rather than as subjects. For this purpose, this study probes the inter-connectedness between the ontological absence of women and animals in patriarchal and national discourses and, using Derrida’s notion of “carno-phallogocentrism” (1995) along with Adams’ seminal work “The Sexual Politics of Meat” (1990), it aims to decipher the fragmentation and consumption of meat/animals (literally) and of women (symbolically) to comprehend how the national discourses are structured around this symbolic devouring that renders women either invisible or irrelevant to these epistemologies. This study throws light on the gendered phallogocentric manifestations of nationalism in Suleri’s memoir and emphasizes that, through the metaphor of meat-less days, Suleri equates the fragmentation and consumption of animals as meat to the fragmentation and symbolic consumption that women have to go through in national narratives and spaces.